PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI WARGA RW 04 KELURAHAN KALIBARU KECAMATAN CILINCING JAKARTA UTARA - Christian, Yulius Evan; Sari, Dini Permata (Pharmacy Action Journal, 2023)
ABSTRACTPHBS is a health behavior that is carried out on awareness so that family members help themselves in the field of health and play an active role in health activities in the community. It is one of the main pillars of a healthy Indonesia and is one of the strategies to reduce the burden on the state, government, and society towards health financing. Healthy conditions can be achieved by changing behavior from unhealthy to healthy and creating a healthy environment; therefore, health needs to be maintained and improved by every member of the household and fought for by all parties. But at this time, there are still many who are attacked by disease due to not implementing clean and healthy living behaviors in the household. The purpose of the study was to determine the level of community knowledge about clean and healthy living behaviors in households. This socialization activity amounted to 19 adults aged 25–60 years in RW 04 Kalibaru Village, Cilincing, North Jakarta. The method of this activity is carried out by means of material presentation, discussion, question and answer, pre-test, and post-test. The results of filling out the pre-test and post-test obtained pre-test results of 61.60% and post-test results of 83.00%. Based on the results of the activity, it can be concluded that there was an increase in the knowledge of the participants, which can be seen from the results of the pre-test and post-test. There was an increase in results from 61.60% to 83.00%. Keywords: Healthy living; Health; Behavior; PHBS